The Hegemony of Knowledge and Islamic Identity Politics: A Critical Discourse Analysis of the Film “Mencari Hilal”: A Critical Discourse Analysis of the Film “Mencari Hilal” - Meutia, Fadhillah Sri; Najamuddin, Najamuddin; Kasogi, Muh. Adnan (Aksiologi : Jurnal Pendidikan dan Ilmu Sosial, 2026)
Identity politics in Indonesia is growing stronger, with religion serving as a primary instrument in the negotiation of power and social legitimacy. This phenomenon is significantly represented in popular culture, one example being the film Mencari Hilal (2021). This study aims to analyze the construction of Islam-based identity politics discourse in the film through the lens of Jäger & Maier’s Critical Discourse Analysis (CDA). The method employed is qualitative with a descriptive-analytical approach, where data was collected through a documentary study of the film’s script, dialogue, and narrative visuals. The findings reveal that the film Mencari Hilal is not merely a religious narrative but a site of knowledge production that validates specific religious authority. The discourse on the determination of the crescent moon is used to construct a dichotomy of “traditional” versus “modern” identities that has real political implications in society. These findings reveal how religious knowledge is constructed to maintain the hegemony of certain groups. The conclusion of this study affirms that the film functions as a political text that reflects the dynamics of power and identity in contemporary Indonesian Islam. Keywords : Critical Discourse Analysis, Identity Politics, Islamic Politics, Mencari Hilal, Jäger & Maier